PENGARUH KEMAMPUAN REPRESENTASI MATEMATIS SISWA TERHADAP KEPERCAYAAN DIRINYA - Sarah Inayah; Gia Adilah Nurhasanah (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2019)
The purpose of this research is to know: (1) Mathematical representation ability and self confidence owned by VII-7 class students of SMP Negeri 2 Cianjur; (2) The Influence of mathematical representation ability on their self confidence of VII-7 class students of SMP Negeri 2 Cianjur. Subjects in this study were 35 students of VII-7 class students of SMP Negeri 2 Cianjur. The research method used in this research is correlation analysis which is causal research by using quantitative approach. Test and non-test data used in data collection technique. Test data were obtained by measuring student’s mathematical representation abilities while non-test data were obtained through questionnaires of self confidene. The correlation coefficient r = 0.761, r2 = 0.579 and the coefficient of determination is 57,9%. Based on it is known that mathematical representation ability give positive influence to self confidene equal to 57,9% while 42.1% influenced other factor not measured in this research. Keywords:  Mathematical Representation Ability, Self Confidence